2021
DOI: 10.1177/10634266211020260
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Investigation of Teacher-Reported Classroom-Level Adversity and Teacher–Student Interactions

Abstract: Early elementary-aged students with and at risk of emotional and behavioral disorders (EBD) tend to develop negative interaction patterns with their teachers. This preliminary study examines the extent to which symptoms of teacher burnout and teacher reports of classroom adversity are associated with the likelihood of negative interactions between teachers and students with and at risk of EBD. We conducted observations to assess teacher–student interactions in individual and group settings, and teachers report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Recently, McLean, Abry, et al (2020) investigated links between classroom adversity and early-career elementary and middle school teacher well-being and found that teachers who reported high levels of adversity also reported more depressive symptoms in their first year of teaching. Granger et al (2021) reported that high levels of classroom adversity increased the likelihood of negative teacher-student interactions with elementary students with and at risk of EBD. Finally, Granger et al (2023) reported a positive relation between teachers' efficacy in instructional strategies and classroom organization quality at low levels of classroom adversity.…”
Section: Classroom Adversity and Classroom Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, McLean, Abry, et al (2020) investigated links between classroom adversity and early-career elementary and middle school teacher well-being and found that teachers who reported high levels of adversity also reported more depressive symptoms in their first year of teaching. Granger et al (2021) reported that high levels of classroom adversity increased the likelihood of negative teacher-student interactions with elementary students with and at risk of EBD. Finally, Granger et al (2023) reported a positive relation between teachers' efficacy in instructional strategies and classroom organization quality at low levels of classroom adversity.…”
Section: Classroom Adversity and Classroom Qualitymentioning
confidence: 99%
“…A larger body of work has examined the influence of classroom adversity on teacher characteristics and teaching practices (Abry et al, 2018; Granger et al, 2021; McLean, Abry, et al, 2020). Abry et al (2018) reported that teacher-reported classroom adversity was negatively related to observations of teachers’ classroom management quality, and teachers in higher adversity classrooms were less effective in preventing disruption and maintaining and regaining order in their classrooms—all essential elements of classroom quality.…”
Section: Classroom Adversity and Classroom Qualitymentioning
confidence: 99%
“…To illustrate, features of the broader classroom context may strengthen or reduce the relation between burnout and teaching practices. In a sample of elementary school classrooms, we investigated teacher’s interactions with students with or at risk for EBD and the extent to which teacher burnout and classroom-level adversity influenced these interactions (Granger et al, 2021). Classroom adversity is a measure of risk exposure and hardship (i.e., ecological risk) experienced among children in classrooms that impacts the academic and socio-emotional outcomes of individual children; this includes factors such as student challenges with family–home life, inadequate nutrition, child health, and disruptive behavior problems (Abry et al, 2018).…”
Section: Best In Class Teacher Burnout and Fidelity Of Implementationmentioning
confidence: 99%
“…Students with EBD may display challenging behavior (e.g., physical aggression, property destruction) that impedes their learning or the learning of others. For this article, we use EBD to describe students with ED, students with EBD, and those at risk for EBD, many of whom receive services in a self-contained classroom setting.Supporting special educators who work with students with EBD in self-contained settings is a priority (Bettini et al, 2020;Conroy et al, 2014;Granger et al, 2021). Bettini et al ( 2019) identified four main concerns related to special educators working with students with EBD in selfcontained settings.…”
mentioning
confidence: 99%
“…Supporting special educators who work with students with EBD in self-contained settings is a priority (Bettini et al, 2020;Conroy et al, 2014;Granger et al, 2021). Bettini et al ( 2019) identified four main concerns related to special educators working with students with EBD in selfcontained settings.…”
mentioning
confidence: 99%